DNA nanotubes and their interaction with membranes: insights through multiscale molecular dynamics simulations - Maingi, V (2016)
DNA origami offers the possibility of developing novel membrane-spanning pores with potential applications in therapeutics and in nanosensors. In this work multiscale molecular dynamics simulation approaches have been employed to understand the dynamics of a DNA nanotube, and of its interaction with lipid bilayer membranes. All-atom simulation studies performed on the DNA nanotube model allowed exploration of its conformational dynamics, and of its interactions with ions and water molecules. Simulations under different conditions (specifically force fields and temperatures) revealed consistent properties in terms of the pore lumen shape and volume, and the gating-like motions at the mouths of the central pore. Overall the DNA nanotube model has been found to be relatively soft and porous in nature. Using the conformational information obtained from these all-atom simulations, a coarse-grained model of the DNA nanotube was developed in order to study its interactions with lipid bilayer membranes on an extended (microsecond) time scale. A number of different hydrophobic anchors which stabilize the nanotube relative to the hydrophobic core of the bilayer have been explored. Local perturbation of the membrane lipids has been observed. Energetic barriers to membrane insertion and exit for DNA nanotubes have been revealed using steered molecular dynamics approaches. A stable membrane- spanning coarse-grain DNA nanopore model was converted to all-atom resolution and used as the basis of simulation to explore the effect of high salt concentration on the stability and conformational dynamics of the pore. This confirmed that the DNA nanotube was stably embedded in the bilayer, and that ions did not form an alternative permeation pathway between the pore wall and the lipids, in contrast with other recently-reported DNA nanopore designs. Overall, these studies contribute to our understanding of the conformational dynamics and membrane interactions of DNA nanopores, thus providing guidelines to design next generation DNA nanopores rendered with controlled gating properties.